Calcule o resultado da expressão 2n + 3n – 5 · (n – 1) para os seguintes valores de n:
a) n = 0
b) n = 3
b) n = −1
Soluções para a tarefa
Respondido por
2
a) 2n + 3n - 5 × ( n - 1 )
n = 0
2 × 0 + 3 × 0 - 5 × ( 0 - 1 )
0 + 0 - 0 + 5
0 + 5
R: 5
b) 2n + 3n - 5 × ( n - 1 )
n = 3
2 × 3 + 3 × 3 - 5 × ( 3 - 1 )
6 + 9 - 15 + 5
20 - 15
R: 5
c) 2n + 3n - 5 × ( n - 1 )
n = - 1
2 × ( - 1 ) + 3 × ( - 1 ) - 5 × ( - 1 - 1 )
- 2 - 3 + 5 + 5
10 - 5
R: 5
Espero ter ajudado!
Perguntas interessantes
Administração,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Português,
1 ano atrás
História,
1 ano atrás
História,
1 ano atrás
Geografia,
1 ano atrás